2023
DOI: 10.1037/cfp0000204
|View full text |Cite
|
Sign up to set email alerts
|

Impact of family, neighborhood, and schools on behavioral health needs of justice-involved Latinx adolescents.

Abstract: Latinx adolescents are overrepresented in the justice system and have high untreated behavioral health needs. We examined the family as well as promotive and inhibitive environments (i.e., neighborhood and school) and their associations on behavioral health among 181 first-time justice-involved Latinx adolescents. Results showed that more optimal caregiver-adolescent attachment was associated with fewer behavioral health needs; more negative caregiver-adolescent communication with greater behavioral health nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 93 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…The mesosystem consists of interactions between various subsystems in a youth's life, including between the family subsystem and other subsystems (see Table 3). For example, a recent study of Latinx JLS-involved youth reported that higher levels of caregiver school contact was linked with greater externalizing concerns; whereas, higher levels of positive caregiver school engagement was negatively associated with externalizing behaviors (Hoskins et al, 2021). This work highlights the need to for investigators to assess for caregiver-school relations in intervention studies.…”
Section: Overview Of Social-ecological Constructsmentioning
confidence: 91%
“…The mesosystem consists of interactions between various subsystems in a youth's life, including between the family subsystem and other subsystems (see Table 3). For example, a recent study of Latinx JLS-involved youth reported that higher levels of caregiver school contact was linked with greater externalizing concerns; whereas, higher levels of positive caregiver school engagement was negatively associated with externalizing behaviors (Hoskins et al, 2021). This work highlights the need to for investigators to assess for caregiver-school relations in intervention studies.…”
Section: Overview Of Social-ecological Constructsmentioning
confidence: 91%
“…Conway et al (2020) found that after separation, adolescents were 4.7 and 3.4 times more likely to report poor relationship quality with their mothers and fathers, respectively. Highlighting the need for treatment, family protective factors might subvert the negative impacts of immigration challenges (Hoskins et al, 2021). More specifically, Calzada et al (2020) found severe externalizing behaviors in children of parents who had experienced adverse immigration environments.…”
Section: Culturally Adapted Interventions To Counter Underutilizationmentioning
confidence: 99%